2007
DOI: 10.4161/auto.4591
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Pompe Disease by Analyzing Single Muscle Fibers: “To See a World in a Grain of Sand…”

Abstract: Autophagy is a major pathway for delivery of proteins and organelles to lysosomes where they are degraded and recycled. We have previously shown excessive autophagy in a mouse model of Pompe disease (glycogen storage disease type II), a devastating myopathy caused by a deficiency of the glycogen-degrading lysosomal enzyme acid a-glucosidase. The autophagic buildup constituted a major pathological component in skeletal muscle and interfered with delivery of the therapeutic enzyme. To assess the role of autophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 34 publications
3
85
0
1
Order By: Relevance
“…Older patients with the slowly progressive form develop severe skeletal muscle weakness and eventually respiratory failure without significant involvement of cardiac muscle. Recent studies have observed that GAA knockout (KO) mice display marked accumulation of autophagic vesicles with altered macroautophagy function (8,15,18). In addition, GAA deficiency causes lysosome enlargement concomitant with the lysosomal accumulation of glycogen (25).…”
mentioning
confidence: 99%
“…Older patients with the slowly progressive form develop severe skeletal muscle weakness and eventually respiratory failure without significant involvement of cardiac muscle. Recent studies have observed that GAA knockout (KO) mice display marked accumulation of autophagic vesicles with altered macroautophagy function (8,15,18). In addition, GAA deficiency causes lysosome enlargement concomitant with the lysosomal accumulation of glycogen (25).…”
mentioning
confidence: 99%
“…In infantile Pompe patients, the enormous build-up of glycogen-filled lysosomes appears to cause the muscle damage (Raben et al 2007). Recent studies showed that autophagy impairment contributes to both disease progression and fibre atrophy (Nascimbeni et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this discrepancy is still not clear, and one possible explanation is that the autophagy build-up in this disease [39][40][41][42] impairs the glycogen clearance in muscle fibers, because the circulating enzyme, which was endocytosed, became trapped in autophagosomes, late endosomes and intermediate autophagosomes, resulting in impaired targeting of the expressed enzyme to the lysosome, 43 leading to partial correction of glycogen storage. Another possibility is that, as in previous studies using AAV vector the glycogen clearance in the heart was complete and in our study it was only partial, 14,15,44 we speculated that maybe some cardiac cells are refractory to LV infection, although this statement needs further investigation.…”
Section: Neonatal Lentivirus Gene Transfer For Murine Gsdii So Kyosenmentioning
confidence: 98%